Higher 30 Day Mortality in Patients with Familial Abdominal Aortic Aneurysm after EVAR. (August 2017) - van de Luijtgaarden, K.M.; Bastos Gonçalves, F.; Hoeks, S.E.; Blankensteijn, J.D.; Böckler, D.; Stolker, R.J.; Verhagen, H.J.M.
Abstract : Objectives: To determine the influence of a positive family history for aneurysms on clinical success and mortality after endovascular aneurysm repair (EVAR). Methods: From 2009 to 2011, 1262 patients with abdominal aortic aneurysms (AAA) treated by EVAR were enrolled in a prospective, industry sponsored clinical registry ENGAGE. Patients were classified into familial and sporadic AAA patients according to baseline clinical reports. Clinical characteristics, aneurysm morphology, and follow-up were registered. The primary endpoint was clinical success after EVAR, a composite of technical success and freedom from the following complications: AAA increase >5 mm, type I and III endoleak, rupture, conversion, secondary procedures, migration, and occlusion. Secondary endpoints were the individual components of clinical success, 30 day mortality, and aneurysm related and all cause mortality. Results: Of the 1262 AAA patients (89.5% male and mean age 73.1 years), 86 patients (6.8%) reported a positive family history and were classified as familial AAA. Duration of follow-up was 4.4 ± 1.7 years. Patients with familial AAA were more often female (18.6% vs. 9.9%, p  = .012). No difference was observed in aneurysm morphology. There was no significant difference in clinical success between patients with familial and sporadic AAA (72.1% vs. 79.3%, p= .116). Familial AAA patients had a higher 30 day mortality after EVAR (4.7% vs. 1.0%, adjusted HR 5.7, 1.8–17.9, p  = .003) as well as aneurysm related mortality (5.8% vs. 1.3%, adjusted HR 5.4, 1.9–14.9, p  = .001), while no difference was observed in all cause mortality (19.8% vs. 24.3%, adjusted HR 0.8, 0.5–1.4, p  = .501). Conclusions: The current study shows a higher 30 day mortality after EVAR in familial AAA patients. Future studies should determine the role of family history in AAA treatment, suitability for endovascular or open repair, and on adaptation of post-operative surveillance. For the time being, patients with familial forms of AAA should be considered at higher risk for EVAR and warrant extra vigilance.